PEMENTASAN JRO GEDE PANEMBAHAN SAKTI DI DESA GUBUG PERSPEKTIF KOMUNIKASI TRANSENDENTAL - Ni Komang Susani; I Nengah Duija; Made Sri Putri Purnamawati Purnamawati (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2021)
Jro Gede Panembahan Sakti staging in Gubug Village, Tabanan District is a dance performance that uses the symbol of a form of Barong Landung or what is called Jro Gede Panembahan Sakti. The issues to be discussed include: (1) What is the process of staging Jro Gede Panembahan Sakti in Gubug Village, Tabanan District, Tabanan ? (2) What elements of communication are contained in the performance of Jro Gede Panembahan Sakti in Gubug Village, Tabanan District, Tabanan Regency? (3) What are the communication implications arising in the performance of JroGedePanembahanSakti in Gubug Village, Tabanan District, Tabanan Regency? Analyze the problem formulation : AestheticÂ by Djelantik, Interersonal CommunicationÂ by Burhan Bungin, and The Dependency Theory of Mass Communication Effects by Ardianto. The methods used to collect data are: observation, interviews, documentation and literature. Â Â Â Â Â The results of the study show that (1) the process of implementing Jro Gede Panembahan Sakti in Gubug Village, Tabanan District, Tabanan Regency, namely: History of Jro Gede Panembahan Sakti where it began during Majapahit government and the entry of other religions that were not Hindu in Majapahit and at that time Bhatara Dalem Majapahit left Majapahit, the form of prerai, gambelan used, clothing, offerings and the process of staging Jro Gede Panembahan Sakti, at the initial stage of preparation, implementation and closing stages. (2) The elements of communication contained in the performance of Jro Gede Panembahan Sakri in the village of Gubug, namely: Communications, Â messages, media, communicants, and feedback, (3) Implications of Communication in the Staging of Jro Gede Panembahan Sakti in Gubug Village, namely: knowledge (knowledge about staging, and learning of Hinduism), Tri Hita Karana implications and religious implication.